EXPRESSION AND PURIFICATION OF DNA POLYMERASE FROM THERMUS THERMOPHILUSINE.COLI EXPRESSION SYSTEM - Li, P.; Abeldenov , S.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2017)
Isolation of thermostable DNA polymerase from Thermusaquaticus was a significant stage in molecular biology and laboratory performance. After Taq DNA polymerase was discovered PCR method became widespread among laboratories around the world. Taq DNA polymerase was the first tool for fast and highly specific amplification of targeted nucleotide sequences. Thus, thermostable polymerases became vital for laboratory performance. We managed to express and purify recombinant Tth DNA polymerase that has both polymerase and reverse transcriptase activities. At first we cultivated Thermusthermophilus strain HB8 and isolated genomic DNA. The gene was amplified and cloned into expression plasmid vector pET-28c(+) under T7 promoter. E.coli cells BL-21(DE3) were transformed with obtained recombinant vector and cultivated with kanamycin antibiotic in LB-broth. Induction was started with IPTG. Cells were disrupted by lysozyme and ultrasonication. Liquid fraction was loaded into sepharose column. Obtained purified enzyme is highly thermostable which was tested in a condition of high temperature and are able to preserve polymerase activity even after heating at 95℃ during 30 minutes. Recombinant Tth polymerase has 95% SDS-PAGE purity. Also we have managed to made different storage and reaction buffers (with various concentrations of salts, stabilizers and detergents) in order to determine the best combination.